Rancang Visual Branding Dan Promosi Animasi 2D Pada Agrowisata Bingin Ambe Koripan - Saputra, Komang Yodi Andira; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2022)
The research is intended to assist the management and staff of Bingin Ambe Koripan Agrotourism in creating 2D animation-based visual identities and promotional videos. Based on interviews with the management of Bingin Ambe Koripan Agrotourism, they need a business identity that can introduce this agro-tourism to tourists and investors, as well as promotional media to provide them with an overview of the concept. Therefore, 2D animation-based visual branding and promotional videos are designed to help promote Bingin Ambe Koripan Agrotourism to visitors and investors in the future. To find out whether the visual branding and promotional videos made are appropriate and suitable for use as a promotional medium for Bingin Ambe Koripan Agro-tourism, the authors conducted a questionnaire to the agro-tourism. From the results of the questionnaire, it can be concluded that as many as 88% of respondents agree that visual branding and promotional videos are suitable for use as promotional media for Bingin Ambe Koripan Agro-tourism, and agro-tourism feel helped by this promotional media because it makes it easier for them to explain agro-tourism to visitors and investors Later.